P153 Association between ustekinumab trough concentrations and clinical, biochemical, and endoscopic outcomes in patients with Inflammatory Bowel Disease. (30th January 2023) - Serra-Ruiz, X; Claudia, H D G; Mayorga Ayala, L; Robles Alonso, V; Céspedes Martínez, E; Casellas, F; Miarons, M; Garcia-Garcia, S; Pérez Martínez, Z; Oller, E; Borruel Sainz, N
Abstract: Background: Ustekinumab (UST), an inhibitor of the p40 subunit of interleukins 12 and 23, is an effective treatment for patients with Crohn's disease (CD) and ulcerative colitis (UC). There is limited data on therapeutic outcomes and UST trough levels (UTL). We aimed to evaluate the association between UTL and corticosteroid-free clinical remission. We also assessed the relationship between UTL and endoscopic remission as a secondary outcome. Methods: We performed a cross-sectional study on IBD patients receiving maintenance therapy with UST (>6 months). We included UTL, C reactive protein (CRP), faecal calprotectin (FC), and clinical and endoscopic indexes (Harvey Bradshaw [HBI] and simple endoscopic score [SES-CD] for CD patients; and partial Mayo score [PMS] and endoscopic Mayo score [EMS] for UC patients). Corticosteroid-free clinical remission (CSF-CR) was defined as HBI<5 or PMS<2 plus normal CRP and/or FC values without corticosteroids. Endoscopic remission was defined as SES-CD<3 or EMS<2. Results: We included 105 patients; the mean age was 50 years, and 59% were female (Figure 1). Eighty-seven patients had CD, and 92% had previously received an anti-TNF. The median time on UST was 121 weeks at inclusion. Sixty-four patients received 90mg subcutaneous (SC) every 4 weeks, 40 patients 90mg SC every 8 weeks, and 1 patient 90mg SC every 12 weeks. Eighty percent were in CSF-CR, and 53% were in endoscopic remission. Median UTL were 2, 7µg/mL (IQR: 1, 7-4, 1µg/mL); UST antibodies were not detected. Patients in CSF-CR and endoscopic remission did not show significantly higher UTL (3, 4µg/mL vs. 2, 5µg/mL, p=0, 147; and 3, 6µg/mL vs. 3, 7µg/mL, p=0, 903, respectively). No differences in UTL were detected between patients on monotherapy and combination therapy (2, 9µg/mL vs. 3, 3µg/mL, p=0, 456). Conclusion: No association between UTL and clinical or endoscopic activity was observed in our predominantly biologic-experienced cohort. Further prospective studies are needed to determine the role of therapeutic drug monitoring while on UST.